The glass ocean : a novel - Williams, Beatriz; Willig, Lauren; White, Karen (Karen S.) (William Morrow, an imprint of HarperColllinsPublishers, 2019)
A "historical mystery, infused with romance, that links the lives of three women across a century--two deep in the past, one in the present--to the doomed passenger liner, RMS Lusitania ... As the Lusitania steams toward its fate, three women work against time to unravel a plot that will change the course of their own lives ... and history itself"--